Pengaruh Kepuasan Kerja, Karakteristik Individu Dan Keterlibatan Kerja Karyawan Terhadap Komitmen Organisasi Pada Biro Pengadaan Barang Dan Jasa Sekretariat Daerah Provinsi Sumatera Barat - Hanif Gusti Syahputra; Prima Yulianti (CV. ITTC INDONESIA, 2025)
This research is a quantitative study using a survey method. This research was conducted with the aim of determining Job Satisfaction, Individual Characteristics and Employee Work Involvement on Organizational Commitment at the Bureau of Procurement of Goods and Services of the Regional Secretariat of West Sumatra Province. The population in the study amounted to 60 people. Data were obtained through questionnaires and the results of the analysis will be presented in tabular form. The sampling technique used the census method. The results of the study indicate that the variable of job satisfaction does not significantly influence organizational commitment, the variable of individual characteristics has a positive and significant effect on organizational commitment, the variable of work involvement does not significantly influence organizational commitment, and job satisfaction, individual characteristics and work involvement together have a significant effect on organizational commitment.